Phytomass estimation of Moroccan rangeland using Sentinel-2 satellite indices and in situ biomass measurements - Mahyou H.; Hachmi A.; Hadria R. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
The monitoring of fodder production in arid and semi-extensive rangelands of Morocco is an essential component of livestock management. An accurate estimate of rangeland phytomass information is required for supplementary feeding leading to sustainable use of rangeland resources. The objective of this study is to test several vegetation indices resulting from remote sensing to propose the most appropriate vegetation indices for phytomass estimation of Moroccan rangelands. Field data, collected during spring 2018 in the Eastern region of Morocco, and eight vegetation indices (ARVI, DVI, IPVI, MSAVI, NDVI, RVI, SAVI and TSAVI) obtained from three Sentinel-2 satellite images acquired in April 2018 are used. Correlations between measured phytomass and each of these vegetation indices were performed to identify the best estimator. The results showed that rangeland phytomass ranged from 0.02 to 4.71 tons with an average of 0.84 tons per hectare in the studied site. Vegetation indices highly correlated with measured phytomass are ARVI, IPVI, NDVI, RVI and SAVI. Also, the results showed that polynomial models were better than linear ones. The best model of phytomass estimation was RVI followed by NDVI with a coefficient of determination, R2, of 0.84 and 0.82, respectively.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)